Effectiveness of Lean Six Sigma Methodology for Optimal Radioisotope Utilization in Nuclear Medicine - Steta, Anjali (Digital Repository of Theses - SSBM Geneva, 2024)
Nuclear Medicine departments offer a large diversity of diagnostic and therapeutic procedures. To remain competitive, health care organizations have promoted the use of Lean and Six Sigma in various settings. Nuclear medicine is facing the challenge of patient management with a better quality of care and there is an enormous need to optimally use the radioisotopes and to improve the process of the nuclear medicine department. The scope of the study was to monitor the optimal utilization of radioisotopes with the potential use of Lean and Six Sigma in the nuclear medicine department. The use of radioisotopes efficiently can be managed with time. There are sub-process steps involved in the department which are coordinated with one another, where the staffs need to speed up their work, which allows more patient scans, reduce the excessive cost for the management, and less wastage in the department. If it is not utilized properly then it is a major issue in the department and affects patient satisfaction and incur more cost to the management. There are 3 objectives mentioned in this study which are: a) To map the process flow of the nuclear medicine department, b) To analyze the bottlenecks or gaps in the workflow with the use of Lean Six Sigma Methodologies and Tools, c) To recommend the solutions to improve the process in the department. v The data collection was done by purposive sampling and mapping process flows with Gemba walk and assessment in the department, observed patient’s time, and recorded turnaround time for each process step in the department. The analysis was done by using Lean Six Sigma methodologies which include Ishikawa Diagram, 5 why’s analysis or technique, lean seven wastes, and calculated Sigma assessment which includes DPU (Defects Per Unit) and DPMO (Defects Per Million Opportunity). Overall results showed that there is a significant difference between the timing of variables and there are major defects that occur due to delays in the department. In conclusion, the sigma level 2.75 which is calculated by DPMO indicates that the nuclear medicine centre is not following the standards and is not competitive enough which needs improvement to sustain in the healthcare industry.